Pendugaan Data Hilang Menggunakan Metode Connected EM-AMMI dalam Bahasa R - Siskha Maulana Basrul; Atus Amadi Putra; Yenni Kurniawati (Journal of Mathematics UNP, 2014)
Abstract –The Multilocation experiment, complete data are estimated with AMMI (Additive Main Effect and Multiplicative Interaction). But, if data in the research is not complete, then it can not be analysis with AMMI. The method can be use in estimator of unbalance data is “ The Method of Connected EM-AMMI with R”. The purpose of estimator from unbalance data with connected EM-AMMI in R is for knowing the procedures of estimator unbalance data in R. The source of data is in the research is the harvest’s result of rice in four cities’s West Sumatra. After that, we get 1.25 % Mean Absolute Percentage Error (MAPE). It shows that the estimator of unbalance data with using connected EM-AMMI’s method. Keywords – AMMI,  connected EM-AMMI, unbalance data, MAPE.